AN ERROR ANALYSIS ON SUBJECT-VERB AGREEMENT ENCOUNTERED IN THESES - Pangga, Wilfred; Sudarsono, Sudarsono; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe objectives of this study are to investigate sorts of error on subject-verb agreement encountered in theses, the error frequency of subject-verb agreement, and the causes of errors of subject-verb agreement. Written language production is the major requirement of a thesis writing. However, sentence types necessarily become the starting points of determination to the correct subject-verb agreement. The research applied a descriptive method with qualitative approach. The data of this research were collected from the corpus of 6 theses submitted to English Language Study Program in Academic Year 2017/2018. The data were manually sorted out by separating subject-verb agreement errors from other types of error. The result showed that there are 6 major forms of subject-verb agreement which comprised 170 errors. Of 6 forms, â€œ3rd singular subjectâ€ was the most frequent encountered in theses. In contrast, â€œdouble subjectâ€ was the least frequent error form. The errors were caused by â€œinterlingual errorsâ€ and â€œintralingual errorsâ€.Â Keywords: Errors, Subject-verb Agreement, Theses